SURAT AL-BAQARAH: REPETISI SEBAGAI PIRANTI KOHESI DALAM AL-QUR'AN - Ma'arif, Samsul (AL ITQAN: Jurnal Studi Al-Qur'an, 2016)
This research is an answer to the notion that the Koran is not systematic and confused book, that  has no cohesion in its topics and themes. This research is seeking for the function of repetition as a device of cohesion in the text of the Koran, particularly in surah al-Baqarah. This research is a library research with data sources from the Koran as a text by using a sample surah al-Baqarah (number 2) as it is written in Mushhaf in circulation today. This study departs from the theory of Halliday and Hasan (1976) of Systemic Linguistics by using methods and techniques of qualitative descriptive analysis. This research indicates that the repetition of language units, either repetition of sounds, especially the form of syllables, repetition of words, phrases, clauses, sentences, and or even repetition of topics, creats a ties that can be combined by the text of the surah al-Baqarah. Through repetition in the surah al-Baqarah cohesion or coherence is found in the level of verses of surah, cohesion in topics surah, cohesion surah al-Baqarah, and even the cohesion of the Koran as a whole.